THE USE OF SHORT STORIES WITH VISUAL MEDIA IN TEACHING ENGLISH FOR THE PRIMARY LEVEL IN SDN 55 PEKANBARU. - Budiyanti, Kurnia; Al Fuadi, Ashabu Thifla; Mahasin, Amirah Nurul Kamilah; Novianti, Mela; Ramadhani, Yolanda Dwi; HSB, Putri Sakinah; Purwati, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of appropriate teaching media is important in improving young learners’ interest and understanding in English learning. One of the teaching strategies that can support English instruction at the primary level is the integration of short stories and visual media. This study aimed to investigate the implementation of short stories with visual media in teaching English at SDN 55 Pekanbaru, as well as to identify students’ responses, advantages, and challenges found during the learning process. This study employed a qualitative descriptive method involving classroom observation and semi-structured interviews with the English teacher. The findings indicated that the use of short stories supported by visual media helped students become more engaged and motivated during classroom activities. Visual media also supported vocabulary development and students’ comprehension of the learning material. However, several challenges were identified, including limited vocabulary mastery among students and inadequate technological facilities in the classroom. In conclusion, the integration of short stories and visual media can create a more interactive and meaningful English learning environment for young learners. Therefore, teachers are encouraged to apply creative and visually supported teaching strategies to improve students’ participation and understanding in English.